Master tracks in different resolutions during POLAR 5 campaign CryoVEx_ANT_2010 - Steinhage, Daniel (Alfred Wegener Institute, Helmholtz Centre for Polar and Marine Research, Bremerhaven, 2017)
This dataset was created via processing of raw position data acquired by the GPS sensor for scientific equipment on Polar 6/Polar 5 to receive a validated master track which is used as reference of further expedition data.